The changes in family functioning and family happiness during the COVID-19 pandemic: The situation in Thailand - Limsuwan, Nida; Prachason, Thanavadee; Wisajun, Pattarabhorn (Frontiers in Public Health, 2022)
Background: The effects of the COVID-19 pandemic on family well-being and functioning were generally concerned by health care providers in many countries. Objectives: To explore the changes in family functioning and family happiness during the pandemic in Thailand and to investigate factors associated with the changes in family happiness. Methods: This was a cross-sectional study conducted between November and December 2021. The online questionnaires regarding family functioning, family happiness, domestic violence and the COVID-19-related experiences were used. Results: A total of 485 participants were included in this study. The perceived family happiness slightly decreased from 8.19 (pre-pandemic score) to 7.62 (post-pandemic score). In contrast, the general family functioning (SCORE-15 index), strength and communication subscale scores after the onset of the COVID-19 pandemic were scored significantly lower than those of the pre-pandemic period. Moreover, the prevalence of verbal and physical violence significantly reduced during the pandemic. In addition, the change in family functioning was the strongest factor associated with the change of family happiness. Conclusion: In general, family functioning slightly improved; however, perceived family happiness decreased during the pandemic. In addition, the change in family functioning was the strongest factor associated with the change of family happiness.